2015
DOI: 10.1101/gr.185132.114
|View full text |Cite|
|
Sign up to set email alerts
|

Retrotransposition creates sloping shores: a graded influence of hypomethylated CpG islands on flanking CpG sites

Abstract: Long interspersed elements (LINEs), through both self-mobilization and trans-mobilization of short interspersed elements and processed pseudogenes, have made an indelible impact on the structure and function of the human genome. One consequence is the creation of new CpG islands (CGIs). In fact, more than half of all CGIs in the genome are associated with repetitive DNA, three-quarters of which are derived from retrotransposons. However, little is known about the epigenetic impact of newly inserted CGIs. We ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 92 publications
(123 reference statements)
5
34
0
1
Order By: Relevance
“…A recent analysis of the Dnmt3l mutant suggests that the loss of DNA methylation at retrotransposon sequences may alter the meiotic chromatin landscape as well as the sites of homologous recombination (22). Unmethylated retrotransposons may also change the expression profile of neighboring genes that are important for meiotic functions, as they can reduce the methylation level at surrounding sites through the formation of sloping shores (45). At the protein level, overexpression of L1 ORF2 protein (ORF2p) is cytotoxic to cultured cells (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent analysis of the Dnmt3l mutant suggests that the loss of DNA methylation at retrotransposon sequences may alter the meiotic chromatin landscape as well as the sites of homologous recombination (22). Unmethylated retrotransposons may also change the expression profile of neighboring genes that are important for meiotic functions, as they can reduce the methylation level at surrounding sites through the formation of sloping shores (45). At the protein level, overexpression of L1 ORF2 protein (ORF2p) is cytotoxic to cultured cells (60)(61)(62).…”
Section: Discussionmentioning
confidence: 99%
“…Cells were gated according to the GFP fluorescence intensity and cell granularity (see supplemental figure S2 in ref. 45). For isolating germ cells from adult animals, an optimized Hoechst 33342-based flow cytometry protocol (51) was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several mechanisms such as DNA and histone methylation and RNAi, actively suppress retrotransposon expression. The epigenetic mechanisms controlling retroelements may well follow retrotransposons during their movement “around” the genome and thereby modify the epigenetic control of retrotransposition targeted loci [59,60]. Below we describe ways of retrotransposon repression that contributed to sculpt the modern genome and its regulatory mechanisms.…”
Section: Retrotransposon-induced Changes In Genome Regulationmentioning
confidence: 99%
“…In this regard, it has been shown that most DNA methylation changes associated with development and cancer do not occur in CpG islands, but rather in sequences up to 2-kb away, which were termed CpG island shores (Doi et al 2009;Irizarry et al 2009). A recent study has shown that hypomethylated CpG islands create sloping CpG island shores (Grandi et al 2015). Interestingly, Alu elements tend to be excluded from promoter regions but are enriched in nearby regions, including CpG island shores.…”
Section: Alu-related Determinants Of Global Genomic Hypomethylation Amentioning
confidence: 99%